2019
DOI: 10.11604/pamj.2019.33.72.18722
|View full text |Cite
|
Sign up to set email alerts
|

"Avoir la peau claire ...…et pourquoi pas? ": dépigmentation volontaire chez les femmes dans une région du sud-ouest du Bénin

Abstract: Introduction Cette étude avait pour objectif de déterminer la prévalence et les facteurs associés à l'usage des produits de dépigmentation volontaire chez les femmes de 15 à 49 ans dans la zone sanitaire de Comè au Bénin. Méthodes Il s'agit d'une étude transversale réalisée en 2016 et qui a concerné 511 femmes âgées de 15 à 49 ans sélectionnées par sondage en grappes. Les données ont été collectées par questionnaire avec des informations sur les caractéristiques démogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The 20–40 age group remains the most concerned in all sub-Saharan African studies. The prevalence of voluntary depigmentation at this age can be explained by the more active search for a partner or the maintenance of a relationship for the purpose of seduction [ 1 7 ]. The trend of females observed in our study has also been reported in most previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 20–40 age group remains the most concerned in all sub-Saharan African studies. The prevalence of voluntary depigmentation at this age can be explained by the more active search for a partner or the maintenance of a relationship for the purpose of seduction [ 1 7 ]. The trend of females observed in our study has also been reported in most previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The trend of females observed in our study has also been reported in most previous studies. Regarding the marital status of our respondents, the desire to be more beautiful, the main goal sought by female practitioners, would be more present among these single women, still looking for a partner, or among married women where there is rivalry between the wives of the same husband in a polygamous context [ 1 4 , 11 , 18 ]. As reported by some authors, women with a high level of education practice voluntary depigmentation more than artisans and housewives.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Numerous adverse effects are associated with skin lightening; these include exogenous ochronosis, bacterial and fungal infections, eczema, dermatitis, scabies, warts, acne, sun damage, body odour, nail dyschromia, infertility, induced Cushing's syndrome, nephropathy, leukaemia, and other cancers. [5][6][7] Numerous reports of morbidity and mortality following years of skin bleaching with hydroquinone, corticosteroids and mercury-containing beauty products have been reported. [8,9] Using skinlightening products may be associated with severe and fatal complications because they are applied on a large body surface area, especially in a warm, tropical environment, which promotes percutaneous absorption of the chemicals.…”
Section: 2023________________________2mentioning
confidence: 99%
“…[17] Similarly, a study conducted in Comè, Benin, among women of reproductive age showed that the motivation for voluntary skin lightening included the drive to appear more beautiful (60.1%), to improve self-esteem (34.1%), the quest to find a spouse (5.9%), to cure acne (35.4%) and to cure hyperpigmentation (11.2%). [7] The adverse effects of skin lightening are numerous and diverse. A study had revealed that the adverse effects included black spots (52.5%), stretch marks (20%), exogenous ochronosis (20%), dyschromia (17.5%) and folliculitis (10%).…”
Section: 2023________________________2mentioning
confidence: 99%
See 1 more Smart Citation